Precommitted Investment Strategy versus Time-Consistent Investment Strategy for a Dual Risk Model. (19th May 2014) - Zhang, Lidong; Rong, Ximin; Du, Ziping
Abstract : We are concerned with optimal investment strategy for a dual risk model. We assume that the company can invest into a risk-free asset and a risky asset. Short-selling and borrowing money are allowed. Due to lack of iterated-expectation property, the Bellman Optimization Principle does not hold. Thus we investigate the precommitted strategy and time-consistent strategy, respectively. We take three steps to derive the precommitted investment strategy. Furthermore, the time-consistent investment strategy is also obtained by solving the extended Hamilton-Jacobi-Bellman equations. We compare the precommitted strategy with time-consistent strategy and find that these different strategies have different advantages: the former can make value function maximized at the original time t = 0 and the latter strategy is time-consistent for the whole time horizon. Finally, numerical analysis is presented for our results.